Populist constitutionalism and constituent power. Issue 2 (25th April 2019) - Doyle, Oran
Abstract: Constituent power is a helpful component of constitutional theory because it provides a conceptual and potentially normative explanation of how a new constitution can be made without any existing legal authority to do so. Contemporary theories of constituent power, however, unhelpfully treat constituent power as a fictive entity, typically the people, that subsists through time. This predominant account of constituent power fails adequately to explain examples of constitution-making and also lends support to the populist claim that a unitary and unchanging people has an immanent but continuing role as a constitutional actor superior to the constitution itself. This enables populist leaders to rely on prevalent understandings of constitutionalism to support the sidestepping and/or removal of constraints on their power. In this Article, I trace the connections between mainstream theories of constituent power and the academically peripheral claims of populist constitutionalism. I argue for a different understanding of constituent power as a capacity that, in principle, may momentarily be exercised by any entity. This explains how a new constitution can unlawfully replace a pre-existing constitution yet come to have lawful authority itself, without implying the diachronic existence of the constituent power as an entity. I illustrate this understanding of constituent power with reference to the constitutional development of Taiwan and Ireland. These examples show—contrary to the predominant account of constituent power—that constitutional systems may be created without the exercise of constituent power and that constitutional law can play an important role in constructing an entity capable of exercising constituent power. Seen in this way, popular references in preambles are important not for their account of how a constitution was made but rather for their account of whom a constitution is for. This account of constituent power undermines core claims of populist constitutionalism. But it also provides a salutary lesson for liberal constitutionalists: a constitution adopted for a people must broadly serve the interests of that people.